Disease-specific perception of fracture risk and incident fracture rates: GLOW cohort study - Gregson, C. L. (2013)
PURPOSE: Accurate patient risk perception of adverse health events promotes greater autonomy over, and motivation towards, health-related lifestyles. We compared self-perceived fracture risk and 3-year incident fracture rates in postmenopausal women with a range of morbidities in the Global Longitudinal study of Osteoporosis in Women (GLOW). METHODS: GLOW is an international cohort study involving 723 physician practices across 10 countries (Europe, North America, Australasia). 60,393 women aged ≥55 years completed baseline questionnaires detailing medical history and self-perceived fracture risk. Annual follow-up determined self-reported incident fractures. RESULTS: In total 2,945/43,832 (6.8%) sustained an incident fracture over 3 years. All morbidities were associated with increased fracture rates, particularly Parkinson’s disease (hazard ratio [HR]; 95% confidence interval [CI], 3.89; 2.78–5.44), multiple sclerosis (2.70; 1.90–3.83), cerebrovascular events (2.02; 1.67–2.46), and rheumatoid arthritis (2.15; 1.53–3.04) (all p<0.001). Most individuals perceived their fracture risk as similar to (46%) or lower than (36%) women of the same age. While increased self-perceived fracture risk was strongly associated with incident fracture rates, only 29% experiencing a fracture perceived their risk as increased. Under-appreciation of fracture risk occurred for all morbidities, including neurological disease, where women with low self-perceived fracture risk had a fracture HR 2.39 (CI 1.74–3.29) compared with women without morbidities. CONCLUSIONS: Postmenopausal women with morbidities tend to under-appreciate their risk, including in the context of neurological diseases, where fracture rates were highest in this cohort. This has important implications for health education, particularly among women with Parkinson’s disease, multiple sclerosis, or cerebrovascular disease.